Do household income related to social well-being among smallholder glutinous rice famers in Langkawi, Malaysia - Jayanti Eka Wardani, Nur Afifah Septiana; Jamaluddin, Askiah; Zainal Badari, Shamsul Azahari; Zainalaludin, Zumilah; Hamsan, Hanina; Samdin, Zaiton (HRMARS, 2024)
This study aimed to explore the impact of income on social wellbeing among farmers in Langkawi, Kedah, engaged in government-supported smart farming practices for glutinous rice cultivation. Conducted across seven villages, the study involved 118 respondents selected via a census approach. Using a survey tool adapted from Radzyk (2014), various dimensions of social wellbeing were assessed, including social connections, neighborhood cohesion, material deprivation, and social isolation. Descriptive statistics and Pearson correlation analysis were employed to analyze the data. The results indicate a strong positive correlation (Pearson coefficient of 0.766, significant at p < 0.01) between household income and social wellbeing, suggesting that higher income levels are associated with increased satisfaction, fulfillment, and positive social interactions. Despite income being a significant predictor, the findings highlight the complex, multifaceted nature of social wellbeing, implying the importance of other contributing factors beyond income alone.